Studi Karakteristik Komposit Matrik Logam Al-Cu-Mg Dengan Penambahan SiC Disintesis Menggunakan Teknik Metalurgi Serbuk Diikuti Artificial Aging - Suprianto; Rasyid Nasution, Bakri; Karo Karo, Junsean Christian; M. Rafli; Kurniawan Nasution, Fadly Ahmad (P3M Politeknik Negeri Cilacap, 2025)
The improvement of the characteristics of Al-Cu-Mg through SiC addition and precipitate formation can be achieved through powder metallurgy and artificial aging, which means that the correct amount of particles and holding time are important. This research aims to investigate the effect of SiC and time on microstructure change, mechanical properties, and electricity. The Al, Cu, Mg, and (1 2.0) wt.%SiC powder were mixed by horizontal milling and subsequent sintering at 500oC. The artificial aging at 180oC with (2, 4, 6) hour holding times. The hardness test, compression, electrical conductivity, and microstructural observation were carried out. The results show that the addition of SiC particles improves the strength and reduces the conductivity. The conductivity improvement obtained after aging. SiC particles tend to be dispersed between grain boundaries. Based on the data, it can be concluded that SiC and artificial aging have a positive effect on the mechanical properties of Al-Cu-Mg alloy.